PERANCANGAN SISTEM INFORMASI PELAYANAN DESIGN BANGUNAN RUMAH PADA PT. SALEMBA DESAINARSITEKTURA - Bimo Aprilianto Sabdono, (2020)
PT. Salemba Design Architectura is one of the consulting services company and contractor in central Jakarta. At the moment there is no computerized system to facilitate the client to process the design of the house building without having to datanng to the location. Therefore, a web-based building design service information system will be designed to facilitate the client to make the booking process effectively and efficiently. With the PIECES analysis method and illustrated with the UML diagram using Waterfall's approach methodology, researchers will build a Web using the Javascript programming language and MongoDB as a database. The result of this research is the planning information system of building design services based on the web to facilitate the client of PT. Salemba Architectural design process without having to come to the location.